How are APOE4, changes in body weight, and longevity related? Insights from a causal mediation analysis - Holmes, Rachel; Duan, Hongzhe; Bagley, Olivia; Wu, Deqing; Loika, Yury; Kulminski, Alexander; Yashin, Anatoliy; Arbeev, Konstantin; Ukraintseva, Svetlana (Frontiers in Aging, 2024)
The ε4 allele of the APOE gene (APOE4) is known for its negative association with human longevity, however, the mechanism is unclear. APOE4 was also linked to changes in body weight, and the latter changes were associated with survival in some studies. Here we explore the role of aging changes in weight in the connection between APOE4 and longevity, using a Causal Mediation Analysis (CMA) approach to uncovering mechanisms of genetic associations. Using the Health and Retirement Study (HRS) data, we tested a hypothesis, whether the association of APOE4 with reduced survival to age 85+ is mediated by key characteristics of age-trajectories of weight, such as age at reaching peak values, and slope of the decline in weight afterwards. Mediation effects were evaluated by the Total Effect (TE), Natural Indirect Effect, and Proportion Mediated. Controlled Direct Effect and Natural Direct Effect are also reported. The CMA results suggest that APOE4 carriers have 19%-22% (TE p=0.020-0.039) lower chances of surviving to age 85 and beyond in part because they reach peak values of weight at younger ages, and their weight declines faster afterwards, compared to non-carriers. This finding is in line with the idea that detrimental effect of APOE4 on longevity is in part related to accelerated physical aging of ε4 carriers.